2020
DOI: 10.4236/ojg.2020.104019
|View full text |Cite
|
Sign up to set email alerts
|

<i>Pakisaurus balochistani</i> (Poripuchia, Slender Titanosauria, Sauropoda) Associated Skeletons Found from the Latest Maastrichtian Vitakri Formation of Pakistan and Referred Fossils from India; Filling of Important Missing Links of <i>Isisaurus colberti</i> Titanosaur Found from Pakistan

Abstract: Recently two slender and medium to large sized titanosaur taxa like Pakisaurus balochistani and Isisaurus colberti of pakisaurids Poripuch along with small sized stocky Saraikimasoom and medium sized stocky Gspsaurus of gspsaurids Poripuch have been recognized from Indo-Pakistan subcontinent.The diagnosis and description of Pakisaurus balochistani and some missing elements of Isisaurus colberti discovered from Pakistan are added here for understanding of possible fuller anatomy of slender titanosaurs. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(62 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…mentioned that although further associations are required. The presently associations from Pakistan and India[23] [24] and reported here revealed that the Pab braincase belongs to Saraikimasoom and this result is consistent with the other cranial and postcranial assignment. The other Indian sauropod genus, Jainosaurus, is represented by braincase material that has been recovered only from central and western India.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…mentioned that although further associations are required. The presently associations from Pakistan and India[23] [24] and reported here revealed that the Pab braincase belongs to Saraikimasoom and this result is consistent with the other cranial and postcranial assignment. The other Indian sauropod genus, Jainosaurus, is represented by braincase material that has been recovered only from central and western India.…”
supporting
confidence: 89%
“…Nicksaurus and Maojandino were established on cranial and associated postcranial materials [18] [19]. Recently four titanosaur taxa were recognized from Indo-Pakistan [20] [21] [22] [23] [24], Vitakridrinda [25] and Vitakrisaurus [25] [26] [27] large sized theropods, Induszalim [25] [28] [29], Pabwehshi [30] and Sulaimanisuchus [25] [26] mesoeucrocodiles, and many other biotas [31] [32] from Pakistan. Due to lack of snout or anterior skull materials from Indo-Pakistan, here the detail description of snout, cranial and postcranial materials from Pakistan are being presented.…”
Section: Introductionmentioning
confidence: 99%
“…Tibia has a rugose proximal end surface that becomes concave and slightly depressed centrally, due to attachement of distal tibial condylar end. The fibular condylar ridge extends down distally as a ridge in Gspsaurus (unlike Pakisaurus [24] and probably Isisaurus from Indo-Pakistan [24]. The distal end of the tibia is quite robust.…”
Section: Description Of Fossils Of Gspsaurus Pakistanimentioning
confidence: 99%
“…Tibia: Fortunately four different types of key tibiae [24] were discovered from Pakistan belonged to distinguish four taxa from Indo-Pakistan like Isisaurus (relatively less transverse width of flattened and slender tibia than Pakisaurus) and Pakisaurus (relatively more transverse width of flattened and slender tibia than Isisaurus) of pakisaurids (transversely narrow and slender tibiae), and Gspsaurus (biconvex lense shaped anteroposteriorly elongated stocky proximal tibia and transversely expanded distal tibia) and Saraikimasoom (subsquare shaped proximal tibia with about equal anteroposterior and transverse widths of stocky proximal tibia and transversely expanded distal tibia) of gspsaurids (transversely broad and stocky tibiae). These four diversities of key tibiae have discarded the hypothesis of only two titanosaurs taxa from Indo-Pakistan the almost equidimensional of the tibia of the somphospondylans Antarctosaurus [62] and Paluxysaurus [63], and transversely broad distal end of tibia of Pakisaurus balochistani [24] and Isisaurus colberti [24] pakisaurids.…”
Section: Description Of Fossils Of Gspsaurus Pakistanimentioning
confidence: 99%
See 1 more Smart Citation